Application of pH and TDS Sensors to the Growth of Red Lettuce (Lactuca sativa var. crispa) in a Hydroponic System - Putri, Amelia Dwi; Fevria, Resti; Anhar, Azwir; Razak, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Red lettuce (Lactuca sativa var. crispa) cultivated using hydroponic systems requires precise nutrient management to optimize growth. Internet of Things (IoT)-based sensors, particularly pH and Total Dissolved Solids (TDS) sensors, enable real-time automatic regulation of nutrient solutions. This study aimed to evaluate the effect of IoT-based nutrient automation using pH and TDS sensors combined with a 50% AB Mix and 50% nano gamal leaf POC formulation on the growth of red lettuce. Data were analyzed using an independent t-test at the 5% significance level. The results showed that all growth parameters in the sensor-based system were significantly higher than those in the manual system (p < 0.05). The automated system improved nutrient balance, increased nutrient absorption efficiency, and maintained stable pH and TDS values throughout the growth period. This study demonstrates that IoT-based nutrient automation effectively enhances hydroponic red lettuce productivity and supports sustainable agricultural practices through efficient resource management. Statistical analysis confirmed significant differences between treatments, indicating that IoT technology improves the efficiency and productivity of hydroponic systems by providing real-time nutrient supply. This research strengthens the potential application of IoT technology in sustainable agriculture and contributes to improved production efficiency and resource savings.